(untitled) (Journal of Parents and Teachers, 2016)
The following article deals with the topic of the birth and its previous process, the gestation. It works on the characteristics of that process, its period of time and the requirements for the result of the gestation will be successful. For that, it suggests different ways to do it which is based on examples of authors and people who have been successful; they have been patient with the gestation’s process and the preparation for the product which has been born.